Radial Stiffness of Combined Journal and Thrust Hydrostatic Bearing. - Sikora, Małgorzata (Lodz University of Technology. Faculty of Mechanical Engineering. Department Division of Dynamics., 2016)
The paper presents the results of theoretical analysis of the effect of supply pressure and rotational speed on the radial stiffness of the integrated angular cylindrical–face hydrostatic bearings designed for precise technological devices. The obtained theoretical results were verified experimentally using the spindle system of the grinding wheel of cylindrical grinder.
Keywords: hydrostatic bearing; combined journal; integrated angular; stiffness; łożysko hydrostatyczne; sztywność promieniowa